The Role of Peer Tutoring in Enhancing Collaborative Skills amongst Learners - Choice Olobo, Jamaica,; Eunice , Victor-Ishikaku, (International Journal on Integrated Education, 2023)
The issue of "collaborating to learn" is tackled by analyzing a peer-tutoring situation aimed at providing help to students with learning difficulties. The tutor and the tutee interactively construct the asymmetry and complementarity of their roles. As a consequence, what seemed at first sight to be the tutor's discursive and guidance abilities appears, upon closer examination, to be the result of the students' interactional work. The benefits of collaboration help to achieve results in the tutor taking charge of the major part of the cognitive work. However, we argue that the mode of collaboration which is accomplished by the learners is also a sign of the representations the tutor and the tutee have a teaching-learning situation as a body of knowledge to be taught and learned. The learning of certain strategies of collaboration which might be expected to enhance learning through peer tutoring should thus be contextualized in social and institutional practices. Developing collaborative skills is a necessary part of training to promote good academic and social performance amongst learners. This paper explains the value of peer tutoring in enhancing collaborative skills among learners majoring in system of education